PENGEMBANGAN BAHAN AJAR POCKET BOOK PADA PELAJARAN IPA KELAS IV SD NEGERI 183 PEKANBARU - Romaya A Siregar; Mahmud Alpusari; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : In school was unavaible teach materials which able to attract student interests. teach materials that ordinary being utilized is packet book. Student does not interest to studying science because packet book that being utilized is thick, many of texts and countain bit of picture and colour. Purpose of this research is to develop teach materials of pocket book in science of fourth grade in SD Negeri 183 Pekanbaru. Type of this research is development research that use 4 D model which consist of define, design, development and disseminate steps. Data of this research gained from result of expert validation, result of questionnaire response and result of student’s pretest-posttest. Pocket book that being designed is given unto experts to see its expediency from material, loanguage, presentation and graphical aspects. Result of expert validations is categories very proper 87,8%. Afterwards pocket book examinated to student in IV A grade SDN 183 Pekanbaru to find out student response and increase N-gain. Experiment results being gained values of response categories very good 84,50% and N-gain 0,54 with medium interpretations which mean there is increasing study result before and after in order to pocket book. Last step to be done disseminate to know student and teacher response widely. Result of response on disseminate steps is category very good 86,68%. Based on that response pocket book that developed able to printed in many amounts and utilized by wider target.Key Words : Development, Pocket Book, 4-D